A Politics of Witnessing: Definitional Ceremony as Social Justice Work in Academia. Issue 3 (November 2021) - Strauven, Sarah
The work outlined in this article has in part evolved as a response to Mr. Behrouz Boochani's call to academics to engage with his work. First, I propose academics consider a form of public engagement drawn from narrative practice as social justice work in academia. In the next section, I illustrate my argument with an Australian case by discussing (a) a peaceful resistance undertaken by the refugees on Manus Island through the lens of definitional ceremony, (b) a public witnessing response by Dr. Surma to the written account of Mr. Boochani of the resistance, and (c) his reply to this act of witnessing. I complement this with my own response to both scholars on account of witnessing their exchanges. In the final section of this article, I articulate in more detail how this proposition of conceiving social justice work in academia is based on a politics of witnessing and acknowledgment. I argue that its epistemological and ontological dimensions hold promise for post-qualitative inquiry and that narrative practices more generally, can assist us in performing relationally situated research.